Nicotinamide Riboside Enhances Endothelial Precursor Cell Function to Promote Refractory Wound Healing Through Mediating the Sirt1/AMPK Pathway - Wang, Zhen-hua; Bao, Xiao-gang; Hu, Jun-jie; Shen, Si-bo; Xu, Guo-hua; Wu, Ye-lin (Frontiers in Pharmacology, 2021)
Lack of vascularization is directly associated with refractory wound healing in diabetes mellitus (DM). Enrichment of endothelial precursor cells (EPCs) is a promising but challenging approach for the treatment of diabetic wounds. Herein, we investigate the action of nicotinamide riboside (NR) on EPC function for improved healing of diabetic wounds. Db/db mice that were treated with NR-supplemented food (400 mg/kg/d) for 12 weeks exhibited higher wound healing rates and angiogenesis than untreated db/db mice. In agreement with this phenotype, NR supplementation significantly increased the number of blood EPCs and bone marrow (BM)-derived EPCs of db/db mice, as well as the tube formation and adhesion functions of BM-EPCs. Furthermore, NR-supplemented BM-EPCs showed higher expression of sirtuin 1 (Sirt1), phosphorylated adenosine monophosphate-activated protein kinase (p-AMPK), and lower expression of acetylated-peroxisome proliferator-activated receptor γ coactivator (PGC-1α) than BM-EPCs isolated from untreated db/db mice. Knockdown of Sirt1 in BM-EPCs significantly abolished the tube formation and adhesion function of NR as well as the expression of p-AMPK and deacetylated-PGC-1a. Inhibition of AMPK abolished the NR regulated-EPC function but had no effect on Sirt1 expression, demonstrating that NR enhances EPC function through Sirt1-AMPK pathway. Overall, this study demonstrates that oral uptake of NR enhances EPC function to promote diabetic wound healing, indicating that NR supplementation might be a promising strategy to prevent the progression of diabetic complications.